カン ホッキョク キコウ ヒカク ニ オケル スバールバル ノ キコウ トクセイ - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi, Takashi (2002)
P(論文) 北極海を巡る各地点での気象・気候条件を比較しつつ, スバールバルの気候特性を明かにすべくレビューを行った。ノルウエー気象研究所によるデータ集から, 国立極地研究所も観測拠点を設けているニーオルスン国際共同観測基地の気候条件を示した。夏冬の気温の年較差が小さく, 年間降水量が多く, 海洋の影響を強く受けていることが特徴である。また, 1910年代以来の長年の気温の変化から, 1910年代から1920年代にかけての昇温は明瞭であるが, 最近30年間の気温上昇はわずかである。これらの特徴を明らかにするために, 北極全域における気候要素の分布を示した。スバールバル地域は, 大気, 海洋いずれにおいても北極海への出入口になっていると共に, 成層圏の極渦の中心近くに位置している。さらに, 1990年代に入って顕著になってきた北極域の気候変化について, 気温上昇から北極振動(AO)の議論まで紹介した。 The climate characteristics of Svalbard are reviewed, based on a circum-polar climate comparison. From the Data Report by the Norwegian Meteorological Institute, climate characteristics of Ny-Alesund, Svalbard, the Japansese where National Institute of Polar Research has an established observation station, are shown. Its climate is characterized by a smaller annual range of air temperature, large annual precipitation, and as maritime Arctic. From the long range variation of temperature since 1910s, a temperature rise in 1910s and 1920s is clear; however, that in the last 30 years has been only minor. In order to explain these characteristics, the distribution of climate parameters is examined. The Svalbard region is characterized by entrance and exit of atmosphere and ocean fluxes, and as the center of the stratospheric polar vortex. Also, recent climate changes in the Arctic including the air temperature rise and Arctic Oscillation (AO) are introduced. departmental bulletin paper